Resemantization of the death ritual from chronicles to contemporary Quechua testimony - Viera Mendoza, Sara (2021)
The descriptions of death made by Guaman Poma, Cieza and Garcilazo de la Vega present common characteristics, such as the embalming of the body, the family gathering at the wake, the remembrance of the deceased’s deeds with mournful songs and the burial with all his belongings. Of all those described, some have lost relevance, such as the respect and care for the body. For this reason, in the testimonies reviewed, the little importance that now acquires the body of the deceased is pointed out with this phrase: “his corpse will be returned”. Others have resemanticized, for example, the objects that the dead person must have to pass to the next life. Now they buy him a suit and tie. They have to wear slippers because these will allow him to run faster to glory. Traditional elements such as songs, food, weeping, family and the importance of the rites to be performed to the body of the deceased lost relevance; however, this has not meant a loss of symbolism or an assimilation of a more westernized vision of what death is, which is why this imaginary still survives in the Quechua testimony and in the symbolism conveyed by some animals that appear in the stories of oral tradition.